2022
DOI: 10.1007/s40264-021-01143-2
|View full text |Cite
|
Sign up to set email alerts
|

Sales of Over-the-Counter Products Containing Codeine in 31 Countries, 2013–2019: A Retrospective Observational Study

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice. Running heading: Trends in sales of over-the-counter codeine in 31 countries Acknowledgements: We thank the Primary Care Research Trust of Birmingham and Midlands Research Practices Consortium for providing the funding to purchase the sales data from IQVIA.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…In line with this research, we found that tramadol and codeine were the fourth and fifth most common opioids implicated in deaths. An analysis of over-the-counter sales of codeine in 31 countries also showed that the UK had the fourth highest rates of sales, 28 which may have contributed to the one in ten codeine-related PFD deaths we identified. A retrospective cohort study of adults in Glasgow, Scotland, showed that the co-occurrence of opioid dependence with homelessness, involvement with criminal justice services, and psychosis was associated with higher rates of premature mortality.…”
Section: Discussionmentioning
confidence: 82%
“…In line with this research, we found that tramadol and codeine were the fourth and fifth most common opioids implicated in deaths. An analysis of over-the-counter sales of codeine in 31 countries also showed that the UK had the fourth highest rates of sales, 28 which may have contributed to the one in ten codeine-related PFD deaths we identified. A retrospective cohort study of adults in Glasgow, Scotland, showed that the co-occurrence of opioid dependence with homelessness, involvement with criminal justice services, and psychosis was associated with higher rates of premature mortality.…”
Section: Discussionmentioning
confidence: 82%
“…The codeine OTC drug sales in 31 countries between 2013 and 2018 [ 12 ] show that what the Japanese spent per capita on codeine purchases ranked fourth, after Ireland, the United Kingdom, and Croatia. The increase in purchases per capita between 2013 and 2018 was the largest among the 31 countries, at over 1000%.…”
Section: Case Study Resultsmentioning
confidence: 99%
“…at pharmacies), purchased online or obtained illicitly. [2][3][4] There are also various conditions that opioids can be used for, including but not limited to, cancer pain, postoperative pain, chronic non-cancer pain, opioid dependence and withdrawal. [5][6][7][8][9] Despite being essential, opioids can cause a number of adverse events from minor (e.g.…”
Section: Introductionmentioning
confidence: 99%